Pembentukan Karakter Siswa Melalui Program Ekstrakurikuler di Madrasah Ibtidaiyaih Sunan Ampel II Maron Kulon - husnah, Rif'atul (ELEMENTARY : Journal of Primary Education, 2024)
. This study aims to explore the process of student character building through extracurricular programs at Madrasah Ibtidaiyah Sunan Ampel II Maron Kulon using a qualitative approach focusing on the role of the mentor teacher and its impact on student character development, especially in the aspects of ethics, social responsibility, and leadership. The research method involved in-depth interviews with supervising teachers, participatory observation in extracurricular activities, and document analysis related to extracurricular programs and the values instilled. The results showed that the extracurricular program at Madrasah Ibtidaiyah Sunan Ampel II Maron Kulon has a significant role in student character building. Supervising teachers play a key role in guiding students in developing values such as honesty, cooperation, and social care through extracurricular activities. In addition, it was identified that students' participation in extracurricular programs strengthens these values through direct experience and practical learning. This research underscores the importance of integrating character education in extracurricular activities as an effective means of shaping student character at Madrasah Ibtidaiyah Sunan Ampel II Maron Kulon.